2012
DOI: 10.1007/s00228-012-1422-3
|View full text |Cite
|
Sign up to set email alerts
|

Impact of regional copayment policy on selective serotonin reuptake inhibitor (SSRI) consumption and expenditure in Italy

Abstract: The implementation of copayment policies in Italy affected both the use and expenditure of SSRIs between 2001 and 2007 to only to a minor extent.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 24 publications
0
5
0
Order By: Relevance
“…Regional differences were also observed in Italy, with a lower percentage of females receiving a prescription for an SSRI in Emilia Romagna than in Tuscany; however, this appears to be in line with regional SSRI prescribing differences observed for the general population. 45 The popularity of paroxetine in Italy and the Netherlands and the absence of a reduction in its prescribing over the study period are surprising, given the number of studies that have demonstrated an increase in the risk of congenital heart defects associated with paroxetine exposure during the early stages of pregnancy. 9,12,46 In the Netherlands, new guidelines on the prescribing of SSRIs during pregnancy were issued in 2012, after the end of our study period; these do not specify a preferred SSRI, but do recommend that, if paroxetine is taken during the periconceptional period, the dose should not exceed 20 mg/day.…”
Section: Discussionmentioning
confidence: 99%
“…Regional differences were also observed in Italy, with a lower percentage of females receiving a prescription for an SSRI in Emilia Romagna than in Tuscany; however, this appears to be in line with regional SSRI prescribing differences observed for the general population. 45 The popularity of paroxetine in Italy and the Netherlands and the absence of a reduction in its prescribing over the study period are surprising, given the number of studies that have demonstrated an increase in the risk of congenital heart defects associated with paroxetine exposure during the early stages of pregnancy. 9,12,46 In the Netherlands, new guidelines on the prescribing of SSRIs during pregnancy were issued in 2012, after the end of our study period; these do not specify a preferred SSRI, but do recommend that, if paroxetine is taken during the periconceptional period, the dose should not exceed 20 mg/day.…”
Section: Discussionmentioning
confidence: 99%
“…The data are weighted by gender and age, allowing us to overcome differences in the demographic structure among regions. Furthermore, the interrupted time series regression analysis allowed us to obtain more valid estimates of the impact of co-payment and national reimbursement criteria on the utilization of statins compared to a pre-post design [1,34,46]. …”
Section: Discussionmentioning
confidence: 99%
“…In the last 20 years, pharmaceutical policies have been mostly driven by the cost-containment imperative. Therefore, a primary research target has been the impact of pharmaceutical policies on public expenditures [ 1 5 ], prices [ 3 , 6 , 7 ] and demand/quantities [ 4 , 5 , 8 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…Literature on the impact of pharmaceutical policies has some limitations. First, most studies focused either on a single therapeutic class [ 8 , 10 12 ] or on the effects of a single policy [ 1 , 3 , 9 ]. Second, the simultaneous impact of different policies [ 11 ] and their effects over time [ 2 ] have not been investigated.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation